2018
DOI: 10.3390/toxics6010013
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Abnormality, Oxidative Stress, and Genotoxicity Induction in the Greenhouse Pesticide Sprayers; Investigating the Role of NQO1 Gene Polymorphism

Abstract: The widespread use of pesticides in agriculture represents a threat to the human populations exposed to them. In this cross-sectional study, the hematological and biochemical parameters, plasma cholinesterase (PChE) activity, oxidative stress, genotoxicity, and NAD(P)H: quinone oxidoreductase 1 (NQO1) C609T polymorphism were measured in 100 greenhouse workers occupationally exposed to pesticide mixture and 104 normal healthy controls. There was a decrease in erythrocytes (5.45%, p = 0.026) and hemoglobin (3.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 66 publications
4
26
1
5
Order By: Relevance
“…The decrease in hematocrit and MCV value could be due to dehydration while increasing WBC, lymphocyte and platelet counts related to infection and stress conditions . In agreement with the earlier studies our study also demonstrates a significant increase in the leukocyte count, lymphocyte absolute count, lymphocyte percentage, MCHC, MPV, PDW and PLCR in pesticide‐exposed agriculture workers . The long term exposure to pesticides may increase the levels of ALT, AST and ALP cause damage to the liver and kidney cells, resulting in hepatic‐toxicity and nephrotoxicity .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The decrease in hematocrit and MCV value could be due to dehydration while increasing WBC, lymphocyte and platelet counts related to infection and stress conditions . In agreement with the earlier studies our study also demonstrates a significant increase in the leukocyte count, lymphocyte absolute count, lymphocyte percentage, MCHC, MPV, PDW and PLCR in pesticide‐exposed agriculture workers . The long term exposure to pesticides may increase the levels of ALT, AST and ALP cause damage to the liver and kidney cells, resulting in hepatic‐toxicity and nephrotoxicity .…”
Section: Discussionsupporting
confidence: 90%
“…Limited number of studies were available to report the pesticide‐induced free radical generation associated with toxicity and other neurobehavioral dysfunctions such as dyslipidemia, hypertension and sleep apnea transformed into neurodegenerative and neurobehavioral outcomes including Parkinson's and Alzheimer's disease in agriculture workers . An increase in the level of lipid peroxidation and decrease in the activity of catalase, GSH and SOD in pesticide‐exposed agriculture workers as observed in the present study suggesting the increased oxidative stress due to pesticide toxicity in exposed agriculture workers and the findings are consistent with the earlier studies . The coefficient correlation analysis demonstrates that the association of AChE with hematological, biochemical and oxidative stress markers have been positively associated with catalase and SOD and negatively linked with the haemoglobin, hematocrit, total RBCs, uric acid, albumin and triglyceroids.…”
Section: Discussionsupporting
confidence: 89%
“…LPO is a destructive selfrepetition chain reaction releasing MDA as its end product [8,9]. This oxidative stress causes DNA damage, chromosomal aberration, and activation of apoptosisrelated markers p53, caspase 3, and 9 [10,11]. Both clinical features and laboratory parameters are very important for accurate diagnosis of cholinesterase inhibitor (ChEI) poisoning and detection of its severity [12].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the more depressed serum AChE activity in OP exposed farm workers, the higher the MDA level and the higher the risk of oxidative damage due to oxidative stress. In contrast, a study of Ahmadi et al found that the inhibition in BuChE activity correlated with the increase in total anti-oxidant capacity [31], and these findings may be explained by the adaptive and defensive responses to the generated free radicals induced by pesticide exposure, respectively. In bivariate analysis, Non-usage of PPE and lack of washing facilities significantly increased risk of abnormal MDA and SOD among the studied agricultural workers by about four times.…”
Section: Subjects and Methods Study Design And Settingsmentioning
confidence: 74%
“…In contrast to these results, some studies found an elevation of SOD levels in exposed group like Simoniello et al [30]. Also, an Iranian study of Ahmadi et al revealed an increase in SOD level to 61.0% [31], and this is attributed to an activation of the compensatory mechanism through the pesticide-induced overproduction of reactive species [28]. The present study revealed that there were no statistical correlations between age, duration of smoking and the number of smoked cigarettes and the levels of BuChE, MDA and SOD (table 2).…”
Section: Subjects and Methods Study Design And Settingsmentioning
confidence: 80%